2009
DOI: 10.1016/j.amjcard.2008.09.105
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Utility of Cardiovascular Magnetic Resonance Imaging in Light-Chain Cardiac Amyloidosis

Abstract: While the presence of abnormal late gadolinium enhancement (LGE) in cardiac amyloidosis has been well established, its prognostic implication and utility to identify cardiac involvement in patients with systemic amyloidosis is unknown. We sought to assess the diagnostic and prognostic significance of cardiovascular magnetic resonance (CMR) imaging in patients with light chain (AL) amyloidosis but unknown cardiac involvement. CMR with LGE was performed in 28 patients with systemic amyloidosis. The presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 15 publications
5
94
0
4
Order By: Relevance
“…There have been conflicting data regarding prognostic value of LGE CMR in cardiac amyloidosis. 23,39,46,47 While some studies failed to establish prognostic value of LGE, other studies have shown that LGE was the only predictor of 1-year mortality (P = .03) beyond ECG and diastology. 23 T1 mapping, on the other hand, seems more robust and a better predictor of outcomes with 90% accuracy, in part due to its superior discriminatory power.…”
Section: Echocardiographymentioning
confidence: 99%
“…There have been conflicting data regarding prognostic value of LGE CMR in cardiac amyloidosis. 23,39,46,47 While some studies failed to establish prognostic value of LGE, other studies have shown that LGE was the only predictor of 1-year mortality (P = .03) beyond ECG and diastology. 23 T1 mapping, on the other hand, seems more robust and a better predictor of outcomes with 90% accuracy, in part due to its superior discriminatory power.…”
Section: Echocardiographymentioning
confidence: 99%
“…36 In addition, cardiac involvement of amyloidosis displays a characteristic pattern of LGE on LGE imaging if the images are acquired four minutes after injection of contrast agent ( figure 4). LGE is found in approximately 70% of patients. 37,38 This ill-defined, generally subendocardial pattern of LGE matches the distribution of the amyloid deposition. 39 Although most profound in the subendocardial layer of the myocardium, amyloid deposition occurs throughout the entire myocardium, and therefore has a higher T1 signal than normal myocardium.…”
mentioning
confidence: 99%
“…However, to additionally perform LGE imaging in these patients has shown to be clinically relevant, since the presence of LGE helps to confirm the diagnosis and also the difference in T1 signal between epicardial and subendocardium is of prognostic importance in cardiac amyloidosis. 37,38 A higher T1 signal in LGE imaging indicates higher amyloid deposition. When amyloid deposition is mainly present subendocardially, than T1 difference between subendocardium and subepicardium is high.…”
mentioning
confidence: 99%
“…In a study by Ruberg and colleagues [ 206 ], which involved 28 patients with systemic AL amyloidosis, 19 patients were found to have DE. Although the presence of DE did not predict mortality (during the median follow-up time of 29 months), the amount of DE, expressed as a percentage of the LV mass, was the strongest independent predictor of the B-type natriuretic peptide level when compared to other LV quantitative factors.…”
Section: Cardiac Amyloidosismentioning
confidence: 97%